Convergence of the parallel chaotic waveform relaxation method for stiff systems - Yuan, Dongjin; Burrage, Kevin (Journal of computational and applied mathematics, 2003)
In this paper, we establish several algorithms for parallel chaotic waveform relaxation methods for solving linear ordinary differential systems based on some given models. Under some different assumptions on the coefficient matrix A and its multisplittings we obtain corresponding sufficient conditions of convergence of the algorithms. Also a discussion on convergence speed comparison of synchronous and asynchronous algorithms is given.